Dynamic behavior of carbon nanofiber-modified epoxy with the effect of polydopamine-coated interface - Wang, Pengfei (2021)
Understanding the dynamic mechanical behaviors of nano-modified composites are essential for designing the anti-collision structures. In this work, carbon nanofibers (CNFs) were coated by mussel-inspired polydopamine ad-layer for modifying the interface and dispersion behaviors while incorporated into epoxy. Quasi-static and dynamic compression mechanical responses of CNFs-modified epoxy were systematically investigated. The polydopamine-coated CNFs composites (D-CNFs/epoxy) show the improved strength and strain energy density in comparison with the pristine CNFs/epoxy. The results also indicate that the yield stress and stress-softening properties of polydopamine-coated-CNFs/epoxy are more sensitive to strain rate compared with the neat epoxy and pristine CNFs/epoxy. An empirical constitutive equation in consideration of the strain rate and the strain-softening was proposed to characterize the stress–strain curve. The equivalent epoxy/filler simulation model was built to reveal that a higher interface friction is beneficial in improving the strength of composites, but deteriorating the strength while the interface friction is lower than a certain value.